DIAGNOSIS ASSISTANCE INFORMATION PROVIDING SYSTEM, DIAGNOSIS ASSISTANCE DEVICE, SYMPTOM INDEX PROVIDING DEVICE, AND SYMPTOM INDEX PROVIDING PROGRAM - YOSHIMOTO SHUSUKE; SEKITANI TSUYOSHI; LIU YIZHI; KIMURA TADASHI; SAWADA KENJIRO (2024)
To provide a symptom index providing device for providing a symptom index on a vasomotor nerve symptom or a depressive symptom of a woman with menopause.SOLUTION: On the basis of brain wave data that changes with time on a sleep period of a subject acquired by an electroencephalograph 10, a sleep stage prediction unit 3110 of a symptom index providing device 3000 determines, with time, which of a plurality of sleep stages the sleep state of the subject is applicable at predetermined time intervals. After data on the sleep stage that changes with time is subjected to smoothing processing, and is converted to a frequency component, a depressive symptom prediction unit 3240 and a menopausal symptom prediction unit 3250 output a symptom index by a learned model generated by machine learning with the frequency component as an input.SELECTED DRAWING: Figure 4 【課題】更年期女性の血管運動神経症状またはうつ症状に関する症状指標の提供をするための症状指標提供装置を提供する。【解決手段】脳波計１０により取得された被検者の睡眠期間についての経時的な脳波データに基づいて、症状指標提供装置３０００の睡眠ステージ予測部３１１０は、被検者の睡眠状態が、複数の睡眠ステージのいずれに該当するかを所定の時間間隔で経時的に判定する。うつ症状予測部３２４０および更年期症状予測部３２５０は、経時的な睡眠ステージのデータがスムージング処理され、周波数成分に変換された後に、この周波数成分を入力として、機械学習により生成された学習済みモデルにより症状指標を出力する。【選択図】図４